PROGRAM PENCEGAHAN DAN PENANGGULANGAN COVID-19 CARE (CHARITY, ACTION, REMINDER, EDUCATION) DI KELURAHAN GEDUNG JOHOR KOTA MEDAN - Dian Fera; Fedia Rizkita; Lili Rahmawati; Siti Khotimah; Lili Eky Nursia N; Danvil Nabela (Jurnal Pengabdian Agro and Marine Industry, 2022)
The low level of public behavior regarding the prevention and control of COVID-19 has led to an increase in the number of cases continuously so that education and promotion regarding the prevention and control of COVID-19 need to  be  carried  out  regularly  to  the  public  in  order  to  reduce  the  rate  of transmission of COVID-19. This service activity is aimed at being a form of concern for the community in the midst of the COVID-19 pandemic, providing knowledge on prevention of transmission of COVID-19 to the public, giving the community the ability to take part in breaking the chain of transmission of  COVID-19. The method of implementing activities is carried out by 4 methods namely Charity, Action, Reminder, Action.  The results of community service were carried out in Kelurahan Gedung Johor, Medan Johor District, Medan City from 15 June - 25 July 2020 with the intended target is people of various ages and each activity has a different target. It seems that the community is enthusiastic in participating in all existing activities. The conclusion is that the implementation of the   COVID-19 Thematic KKN is going well in every activity   program implemented. This program is expected to increase public understanding of the prevention and control of COVID-19 in Kelurahan Gedung Johor which is one of the kelurahan with the red zone category in Medan City.